Growth and Innovation of Competitive Regions - Fratesi, Ugo (Springer, 2017)
This volume investigates the dynamics of regional performance in advanced countries and the mechanisms that allow some regions to grow more rapidly than others, to become and remain more competitive in the long run. The authors show how the capability of regions to innovate is enhanced by a large number of factors, including entrepreneurship, clustering, creativity, new technologies, human capital and the presence of internal, intra-regional, and external, extra-regional, connections. The book is mainly theoretical, but all chapters also analyze the policy consequences. Moreover, the empirical results reinforce the theoretical findings and as such are more broadly applicable and not bound to the specific case. The general reach of the theoretical arguments, and the focus on policy consequences, make this book helpful for both scholars and policymakers.